The Role of Institutional Innovation in Madukismo Sugar Industry Toward The Sugarcane Farming Production in The Province of Jogjakarta - Unggul Priyadi (Economic Journal of Emerging Markets, 2008)
This research aims are, first analyzing the factors affecting farmers’ opportunities to adopt sugarcane farming organization as considered by Madukismo SP and the second determining the transactional cost of TR Kemitraan, the organization of TR KSU, and the organization of sugarcane farming as Autonomy (TR Mandiri). Research’s findings is farmers’ opportunity to adopt Madukismo SP’s sugarcane farming organizational innovation has been simultaneously affected by sugarcane land wide transaction cost, rendement, the experience of managing sugarcane farming, and respondent education. Considering the transaction cost charged against sugarcane farmers, the farmers with the farming of TR Mandiri bear the higher transaction cost than farmers who adopt the farming of TR KSU and TR Kemitraan.Keywords: Multinomial logistic regression, transaction cost, sugarcane farming as business cooperation (TR KSU) and sugarcane farming as partnership (TR Kemitraan), sugarcane farming as Autonomy (TR Mandiri).